2020
DOI: 10.1002/aqc.3341
|View full text |Cite
|
Sign up to set email alerts
|

Restoring wetland biodiversity using research: Whole‐community facilitation by beaver as framework

Abstract: 1.Wetlands are declining worldwide, and there is a great need for their restoration and creation. One natural agent of wetland engineering is beavers, Castor spp., which have returned or are returning to many parts of their former range. 2.We initially studied the facilitative effect of the beaver Castor canadensis on a waterbird community consisting of three waders and four ducks in boreal wetlands in southern Finland. Both waterbird species diversity and abundance increased when beavers impounded a pond. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…Restoring beavers to areas they have been extirpated from has received attention as a natural framework for achieving ecological restoration objectives. Beaver‐assisted restoration has been touted as a tool for repairing incised and degraded stream systems throughout the western USA and parts of Eurasia (Burchsted et al 2010, Pollock et al 2014), while others have advocated for using beavers to rewild ecosystems (Law et al 2017, Willby et al 2018) and facilitate wetland biodiversity (Nummi and Holopainen 2014, 2020, Law et al 2019). We suggest beaver engineering could be used to increase surface water storage and promote freshwater conservation efforts in forested ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring beavers to areas they have been extirpated from has received attention as a natural framework for achieving ecological restoration objectives. Beaver‐assisted restoration has been touted as a tool for repairing incised and degraded stream systems throughout the western USA and parts of Eurasia (Burchsted et al 2010, Pollock et al 2014), while others have advocated for using beavers to rewild ecosystems (Law et al 2017, Willby et al 2018) and facilitate wetland biodiversity (Nummi and Holopainen 2014, 2020, Law et al 2019). We suggest beaver engineering could be used to increase surface water storage and promote freshwater conservation efforts in forested ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…25,000 km 2 of new aquatic pond habitat and 550,000 km of riparian interface have been created in boreal and temperate zones (Whitfield et al 2015). Beavers have been proposed as a tool for biodiversity conservation (Law et al 2019;Nummi and Holopainen 2020), and several studies have shown that beavercreated succession can affect aquatic invertebrates in a beaver-modified landscape at a general level (Bush et al 2019;Washko et al 2020). One of the first studies to focus on a specific taxon of aquatic invertebrates found a difference in water beetle abundance in beaver wetlands and non-beaver wetlands (Willby et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…процессы и функции лесов Роль животных в функционировании наземных экосистем, в том числе лесных, оценивалась в работах многих исследователей (Гиляров, 1951;Гиляров, Криволуцкий, 1985;Исаев и др., 2015;Isaev et al, 2017;Стриганова, 1980Стриганова, , Edwards et al, 1995Динесман, 1961;Ходашева, Елисеева, 1970;Формозов, 1976;Млекопитающие…, 1985;Абатуров, 1984;Раститель-ноядные…, 1986;Торопова, 1994;Бобровский, 2010;Горнов, 2013;Шевченко, 2016;Kurek, 2019;Saikkonen et al, 2019;Evstigneev, Solonina, 2020;Nummi, Holopainen, 2020 1994,2004).…”
Section: влияние животных на экосистемныеunclassified
“…Крупномасштабные изменения в современном лесном биогеоценотическом покрове производят бобры (Castor fiber). Средопреобразующие воздействия бобров проявляются на всех пространственных уровнях (Торопова, 1994;Смирнова, 1998;Wright et al, 2002;Восточноевропейские..., 2004;Завьялов и др., 2005;Алейников, 2010;Завьялов, 2013;Логофет и др., 2014 Сооружения бобров активно используются сухопутными, околоводными и водными животными (Nummi et al, 2011;Nummi, Holopainen, 2020). Например, бобровые пруды во время засухи служат водопоями для птиц и зверей.…”
Section: ландшафтный уровеньunclassified